CLINICAL AND FUNCTIONAL FEATURES OF PATIENTS WITH ISOLATED SYSTOLIC HYPERTENSION - E. S. Mazur; V. V. Mazur; D. Yu. Platonov; D. V. Kileynikov; T. Yu. Timeshova (Рациональная фармакотерапия в кардиологии)
Aim. To compare vasomotor endothelial function, aortic elastic properties and characteristics of left ventricular (LV) remodeling in patients with isolated systolic (ISHT) and sistolo-diastolic (SDHT) hypertension. Material and methods. Echocardiography , assessment of aorta elastic properties and endothelial vasomotor function were performed in 24 ISHT patients (mean age 73.6 years, mean disease duration 24.8 years) and 52 SDHT patients (mean age 58.0 years, mean disease duration 12.8 years). The age of hypertension onset did not differ significantly in patients of both groups. Results. Aorta elastic coefficient in ISHT patients was 6 times lower than this in SDHT patients (1.00 vs 6.36 mm2/mm Hg, respectively), and vasodilation coefficient (which reflects an ability of vessels to expanding in response to blood flow acceleration) less on 35% (10.9 vs 16.8 standard units, respectively). Patients of ISHT and SDHT groups did not differ in thickness of the interventricular septum (14.8 vs 14.3 mm, respectively), and LV ejection fraction (59.9 vs 60.4%, respectively). However , LV posterior wall thickness in ISHT patients was 3.0 mm less than this in SDHT patients, as well as amplitude of systolic displacement of LV fibrous ring (which reflects LV longitudinal systolic function) was 0.9 cm bigger , respectively. Conclusion. Elderly age, aorta high stiffness, asymmetric LV hypertrophy and impaired LV longitudinal systolic function are typical clinical and functional features of ISHT patients.